Catalysis in a Cage: Condition-Dependent Speciation and Dynamics of Exchanged Cu Cations in SSZ-13 Zeolites - Paolucci, Christopher; Parekh, Atish A; Khurana, Ishant; Di Iorio, John R; Li, Hui; Albarracin Caballero, Jonatan D; Shih, Arthur J; Anggara, Trunojoyo; Delgass, W. Nicholas; Miller, Jeffrey T; Ribeiro, Fabio H; Gounder, Rajamani; et al. (Journal of the American Chemical Society, 2016)
The relationships among the macroscopic compositional parameters of a Cu-exchanged SSZ-13 zeolite catalyst, the types and numbers of Cu active sites, and activity for the selective catalytic reduction (SCR) of NO x with NH3 are established through experimental interrogation and computational analysis of materials across the catalyst composition space. Density functional theory, stochastic models, and experimental characterizations demonstrate that within the synthesis protocols applied here and across Si:Al ratios, the volumetric density of six-membered-rings (6MR) containing two Al (2Al sites) is consistent with a random Al siting in the SSZ-13 lattice subject to Löwenstein’s rule. Further, exchanged CuII ions first populate these 2Al sites before populating remaining unpaired, or 1Al, sites as CuIIOH. These sites are distinguished and enumerated ex situ through vibrational and X-ray absorption spectroscopies (XAS) and chemical titrations. In situ and operando XAS follow Cu oxidation state and coordination environment as a function of environmental conditions including low-temperature (473 K) SCR catalysis and are rationalized through first-principles thermodynamics and ab initio molecular dynamics. Experiment and theory together reveal that the Cu sites respond sensitively to exposure conditions, and in particular that Cu species are solvated and mobilized by NH3 under SCR conditions. While Cu sites are spectroscopically and chemically distinct away from these conditions, they exhibit similar turnover rates, apparent activation energies and apparent reaction orders at the SCR conditions, even on zeolite frameworks other than SSZ13.